2008
DOI: 10.21273/horttech.18.1.80
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Methyl Bromide Alternatives in Strawberry

Abstract: Field studies were conducted to compare the performance of several methyl bromide (MBr) alternative programs on sting nematode (Belonolaimus spp.) control and marketable yield of ‘Camarosa’ strawberry (Fragaria ×ananassa). The tested fumigation programs were 1) MBr + chloropicrin (Pic; 67:33 v/v) at 350 lb/acre, 2) Pic + metam sodium (MNa) at 300 lb/acre and 37.5 gal/acre, 3) 1,3-dichloropropene (1,3-D) + Pic at 35 gal/acr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 7 publications
1
12
0
Order By: Relevance
“…Improvements in CP and AITC regarding pest control efficacy by mechanical placement manipulation reported in previous work (Gilreath et al, 2008;Jacoby, 2016;Papiernik et al, 2004;Rodriguez, 2002;Yates et al, 2002) may be dependent on adjusting the sorption/ desorption equilibrium in the soil. Our research suggested that when surfactants are present in the soil-water-chemical phase, the hydrophilic side bonds with water, the lipophilic side bonds with hydrophobic soil particles, and the hydrophobic particles of the chemical allow less adsorption of chemicals on soil particles, thereby allowing greater mobility of fumigants through the soil.…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…Improvements in CP and AITC regarding pest control efficacy by mechanical placement manipulation reported in previous work (Gilreath et al, 2008;Jacoby, 2016;Papiernik et al, 2004;Rodriguez, 2002;Yates et al, 2002) may be dependent on adjusting the sorption/ desorption equilibrium in the soil. Our research suggested that when surfactants are present in the soil-water-chemical phase, the hydrophilic side bonds with water, the lipophilic side bonds with hydrophobic soil particles, and the hydrophobic particles of the chemical allow less adsorption of chemicals on soil particles, thereby allowing greater mobility of fumigants through the soil.…”
Section: Resultsmentioning
confidence: 85%
“…To increase the efficacy of isothiocyanate generators, most research suggested that residence time and concentration need to be increased (Nelson et al, 2013). Methods of mechanical manipulation of fumigant placement in the soil, including using multiple drip lines, increasing water volume, increasing the depth of application, and using total impermeable film to prevent the fumigant from escaping into the atmosphere (Gilreath et al, 2008;Jacoby, 2016;Papiernik et al, 2004;Rodriguez, 2002;Yates et al, 2002), have been reported in the literature. Although some of these techniques showed some potential for improving the efficacy of AITC and CP, the efficacy is still inconsistent because AITC and CP are not soluble in water (Isagro, 2016;Saeed et al, 1997); therefore, we assumed that, when applied to the soil, CP and AITC are strongly adsorbed on the soil particles.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…compared with the MeBr standard, but control of nutsedge was not as good as the standard. Also in Florida, researchers studied alternative treatments for strawberry production (Gilreath et al 2008). 1,3-D plus chloropicrin and dazomet, 1,3-D plus Pic, Pic and metam sodium, and fosthiazate (an OP nematicide) and Pic proved to be as valuable as the grower-standard MeBr plus Pic on strawberry plant vigor, sting nematode control, and early and total marketable yields.…”
Section: Mebr Alternatives For Preplant Applicationsmentioning
confidence: 99%
“…Traditional nematicides that are registered for use in the United States include fosthiazate, oxamyl, and 1,3dichloropropene (1,3-D). Fosthiazate has been shown to effectively control plant-parasitic nematodes in a diversity of crops, including potato [Solanum tuberosum (Ingham et al, 2000) •ananassa (Gilreath et al, 2008)]. Oxamyl is labeled for use in perennial crops such as apple (Malus spp.…”
mentioning
confidence: 99%